Predictive Model of Tibial Nerve Depth for Needle-Based Interventions With Broader Applications: An Observational Study in a Spanish Cohort - Isabel Mínguez-Esteban; Carlos Romero-Morales; Jorge Hugo Villafañe; Juan Antonio Valera-Calero; Gustavo Plaza-Manzano; Ángel González-de-la-Flor (International Journal of Clinical Practice)
Conclusion: This predictive model shows that leg girth and gender are significant predictors of tibial nerve depth in a healthy cohort. However, its clinical utility remains preliminary and requires external validation in larger, diverse, and pathology-specific populations to confirm broader applicability in clinical settings.